Prevalence and Patterns of Dyslipidemia in West District of Delhi: Prospective Study for Lifestyle Modification to Prevent Heart Disease - Vineet Banga; K Gloria T Ro (Indian Journal of Medical Biochemistry)
Introduction: Dyslipidemia involves abnormal blood lipid levels, such as high cholesterol, high triglycerides, high low-density lipoprotein (LDL), and low high-density lipoprotein (HDL). It can be genetic (primary) or due to other diseases (secondary). Atherosclerosis causes artery narrowing from cholesterol-rich plaque buildup, reducing blood flow to the heart and leading to cardiovascular disease (CVD). Cardiovascular disease is one of the most common causes of death worldwide, and dyslipidemia contributes as a major risk factor to it. Effective therapies and public awareness are key to prevention. Aim: To study the prevalence of dyslipidemia in population visiting the hospital in West District of Delhi and to recommend lifestyle modifications to the population visiting the hospital to prevent heart disease. Materials and methodology: A cross-sectional study in outpatient department and inpatient department, Acharya Shree Bhikshu Government Hospital (Government of NCT of Delhi), Moti Nagar, New Delhi (n = 1,650, male = 931; females = 719) for period of 4 months (from 1st June 2024 to 30th September 2024). Results: Of the subjects studied, 22.18% had hypercholesterolemia, 40.78% had hypertriglyceridemia, 36.55% had low HDL, 14% had high LDL levels, 31.64% had high total cholesterol-HDL ratio and 70.42% had abnormalities in one of the lipid parameters. Conclusion: Prevalence of dyslipidemia is very high, therefore, regular screening of patient's lipid profile and healthy lifestyle promotion is strongly recommended to prevent heart diseases and other noncommunicable diseases (NCD).